Impact of Delayed Cord Clamping on Neurodevelopmental Outcomes at 2 Years in Preterm Infants - Nabi, Siraj; Javeed, Asif; Ali, Husnain; Mal, Chhinkoo; Basit, Muhammed (Journal of Neonatal Surgery, 2024)
Background: To assess the effect of delayed versus early cord clamping on neurodevelopmental outcomes at two years of age in preterm infants. Methods: This study was carried out at People's University of Medical and Health Sciences Nawabshah between June 2023 and June 2024. 73 preterm infants born at < 37 weeks of gestation were included. Participants were divided into DCC (≥30 seconds) and ECC (<30 seconds) groups based on the timing of cord clamping. Some of the outcomes were ‘recorded immediately and neurodevelopmental outcomes were assessed at 24 months with the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III)’. The differences of the groups were analyzed using appropriate statistical methods, and a p-value <0.05 was considered significant. Results: Infants in the DCC group had significantly higher hemoglobin levels at 24 hours (p < 0.001) and lower rates of blood transfusion (p = 0.014) and intraventricular hemorrhage (p = 0.037). At two years, DCC infants showed significantly better cognitive (p = 0.032) and motor scores (p = 0.045). Language delay and cerebral palsy were lower in the DCC group, though not statistically significant. Conclusion: Delayed cord clamping is associated with favorable hematological and neurodevelopmental outcomes in preterm infants. Its implementation in delivery practices may contribute to improved long-term developmental trajectories in this vulnerable population